Recent Developments on Multi-Functional Metal-Free Mechanochromic Luminescence and Thermally Activated Delayed Fluorescence Organic Materials - Barman, Debasish; Gogoi, Rajdikshit; Narang, Kavita; Iyer, Parameswar Krishnan (Frontiers in Chemistry, 2020)
Metal-free organic compounds with highly ordered π-conjugated twisted skeletons are capable of generating brilliant multi-colored light. Additionally, the co-existence of numerous other multi-functional properties have endowed them potentially as promising class of materials for several electronic and photonic applications and next-generation advanced luminescent material based devices. This review highlights the recent developments on these fascinating class of multi-property encompassing materials involving highly twisted donor-acceptor based single molecular platform with synchronized photophysical behavior like thermally activated delayed fluorescence (TADF), mechanoresponsive (MR), room-temperature phosphorescence (RTP) and aggregation induced emission (AIE) with associated unique inherently manifested structure-property relationship investigations. Furthermore, a brief summary of the optoelectronic behavior of TADF materials is also presented by correlating their performances in the organic light-emitting diodes (OLEDs) and corresponding EL devices. In addition to mechanochromic luminescence (MCL) with TADF behavior, new types of emitters are also being developed, with tunable color changes such as blue-green, yellow-orange, yellow-red, etc. with some emitters crossing the entire visible span to produce white OLEDs. These developments have enriched the library of fascinating organic materials in addition to provide new directions of multifunctional material design for solutions processed OLED and several other advanced devices.